APPLICATION DESIGN SYSTEM ADMINISTRATION HOSPITAL PATIENTS IN HOSPITALS SARI ASIH USING MICROSOFT VISUAL BASIC PROGRAMMING LANGUAGE 6.0 - Angga Surya Pratama; Elly Agustina,. Skom,. MMSI Elly Agustina,. Skom,. MMSI (Jurnal Sistem Informasi, 2009)
In essence the hospital during this asih Mampang Depok administration in patientsreceiving inpatient care is still done manually so often cause errors in the delay ofpatient care information.Based on these problems, I am interested to try to help resolve pemasalahan bycreating a computerized system and the author will use the display programanmicrosoft Visual Basic 6.0.